Comparison of ARIMA and Artificial Neural Networks Models for Stock Price Prediction - Ayodele Ariyo Adebiyi; Aderemi Oluyinka Adewumi; Charles Korede Ayo (Journal of Applied Mathematics)
This paper examines the forecasting performance of ARIMA and artificial neural networks model with published stock data obtained from New York Stock Exchange. The empirical results obtained reveal the superiority of neural networks model over ARIMA model. The findings further resolve and clarify contradictory opinions reported in literature over the superiority of neural networks and ARIMA model and vice versa.